2020
DOI: 10.1038/s41598-020-64612-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Mobilized Colistin Resistance using a Nucleic Acid Based Lab-on-a-Chip Diagnostic System

Abstract: The increasing prevalence of antimicrobial resistance is a serious threat to global public health. One of the most concerning trends is the rapid spread of Carbapenemase-Producing Organisms (CPO), where colistin has become the last-resort antibiotic treatment. The emergence of colistin resistance, including the spread of mobilized colistin resistance (mcr) genes, raises the possibility of untreatable bacterial infections and motivates the development of improved diagnostics for the detection of colistin-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…29, the presented device is also a quantitative test, providing information on the viral load, which is an important indicator of the patient's infectivity. Furthermore, the proposed PoC diagnostic test can be rapidly adapted for the detection of other respiratory pathogens or infectious diseases (22)(23)(24) as only a target-specific LAMP assay has to be incorporated. This inherent capability promotes versatility and improves scalability, offering a wide range of applications that can be easily integrated for the simultaneous multiple detection of pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29, the presented device is also a quantitative test, providing information on the viral load, which is an important indicator of the patient's infectivity. Furthermore, the proposed PoC diagnostic test can be rapidly adapted for the detection of other respiratory pathogens or infectious diseases (22)(23)(24) as only a target-specific LAMP assay has to be incorporated. This inherent capability promotes versatility and improves scalability, offering a wide range of applications that can be easily integrated for the simultaneous multiple detection of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a barrier to the implementation of portable devices for SARS-CoV-2 PoC diagnostics, which can be overcome by using label-free electrochemical-based DNA detection. Recently, in Rodriguez-Manzano et al (23), we reported an embedded Lab-on-Chip (LoC) device for label-free biosensing applications which consists of ion-sensitive fieldeffect transistors (ISFETs) manufactured in unmodified complementary metal-oxidesemiconductor (CMOS) technology (24). This device has integrated thermal management and is capable of nucleic acid detection by monitoring pH changes that occur during nucleic acid amplification which are compatible with isothermal assays.…”
Section: Introductionmentioning
confidence: 99%
“…27 Lab-on-chip, discs and cards can effectively bypass inadequate human resources, infrastructure and sometimes cold-chains. 28 The GeneXpert MTB/RIF platform is an example of one such leapfrog technology and the BioFire FilmArray represents another. The former has been more widely deployed in LMIC settings and consists of automated PCR system initially and most commonly used for tuberculosis diagnostics and rifampicin sensitivity testing.…”
Section: Promises and Pitfalls Of Nucleic Acid Amplification Testsmentioning
confidence: 99%
“…Recently, we have introduced a new smartphone-based lab-on-a-chip (LoC) platform, offering an affordable and portable alternative to gold-standard laboratory-based instruments for detection of infectious diseases (19). This platform combines ion-sensitive field-effect transistors (ISFETs), fabricated in unmodified complementary metal-oxide semiconductor (CMOS) technology, with loop-mediated isothermal amplification (LAMP) and an AndroidOS application for data acquisition, visualization and cloud connectivity.…”
Section: Introductionmentioning
confidence: 99%